The integration of technology into ELT: a case of STBA’s lecturers - Lini Fitri; Yohanes Gatot Sutapa Yuliana; Sudarsono Sudarsono (UPT Bahasa Universitas Tanjungpura, 2022)
Technology has had a major impact, especially on education. The integration of technology into ELT to facilitate the learning and teaching process has become a more and more popular trend. This research was a case study designed to explore the integration of technology into ELT by the lecturers of STBA Pontianak. The data were gathered from 3 full-time lecturers at the STBA Pontianak using semi-structured interviews, observation, and audiovisual materials. The research found out that the lecturers of STBA Pontianak had positive perceptions towards the integration of technology into ELT due to their belief in technology-enhanced language learning, technology knowledge, and understanding; two of them have been integrating technology as transformation (modification and redefinition) tools in its pedagogical processes; and the constraints of integrating technology into ELT dealt with the limited resources, time, internet access, and the technology that did not fit with the courses. It is suggested that the lecturers work in collaboration with each other to share ideas and teaching strategies, as wells as to integrate the technology into ELT.